Tachycardia-induced cardiomyopathy in pregnancy. Issue 10 (October 2016) - Joseph, Anil C.; Prapa, Matina; Pellicori, Pierpaolo; Mabote, Thato; Nasir, Mansoor; Clark, Andrew L.
Abstract : Heart failure in pregnancy is rare, but usually ascribed to peripartum cardiomyopathy in the absence of other possible diagnoses. However, heart failure can develop solely due to a tachycardia, so-called 'tachycardia-induced cardiomyopathy'. The incidence of tachycardia-induced cardiomyopathy in pregnancy is unknown, but it is a treatable and potentially reversible cause of heart failure. Clinically, tachycardia-induced cardiomyopathy during pregnancy might present in a similar manner, but its management has to be individualized according to the arrhythmic substrate and usually involve multidisciplinary input from specialists in obstetrics, cardiac electrophysiology and heart failure.